Sinais clínicos em pacientes com espondiloartrites na presença e na ausência do gene HLA-B*27 - Toledo, Ricardo Acayaba de (2013)
Introduction: Spondyloarthritis is a group of diseases with clinical, laboratory and image similar. Analysis of clinical manifestations of spondyloarthritis in patients with and without the HLA-B*27 were performed, but the results revealed great heterogeneity. Objectives: The aim of this study was to evaluate the clinical manifestations of spondyloarthritis according to the classification criteria of the European Study Group Spondyloarthropathy (ESSG) in the presence and absence of the HLA-B*27. Patients and methods: From a total of 156 patients with clinical suspicion referred for the investigation of gene HLA-B*27, 73 were diagnosed with spondyloarthritis according to the criteria of ESSG. The HLA-B*27 were identified using commercial kits (Dynal ReliTM SSO HLA-B Typing Kit, Invitrogen). Clinical data were collected from medical records of patients. The results were compared using the chi-square or Fisher exact test. The values of Odds Ratio (OR) and confidence interval of 95% were also calculated. The p-value equal to or less than 0.05 was considered significant. Results: Of the 73 selected patients, 53 (72.6%) were male and 20 (27.4%) were female. The mean age was 49.4 and did not differ between genders (p = 0337). The spondyloarthritis found among the 73 patients were: ankylosing spondylitis (n = 47; 64.4%), psoriatic spondyloarthritis (n = 9; 12.3%), undifferentiated spondyloarthritis (n = 9; 12.3%), spondyloarthritis enteropathica (n = 6; 8.2%) and reactive arthritis (n = 2; 2.7%). The average age of onset was equal to 39.1 (± 11.7) and did not differ between genders (p = 0.9057). Of the total, 35 (47.9%) patients were HLA-B*27 positive and 38 (52.1%) were negative. This gene was positively associated with ankylosing spondylitis (OR: 5.37, 95% CI: 1813-15905, p = 0.003) and negatively with spondyloarthritis enteropathica (OR: 0.07, 95% CI: 0003-1301, p = 0.025). The sacroiliitis was associated with the presence of the gene (OR: 10 552, 95% CI: 1260-88256, p = 0.014) and intestinal injury absence (OR: 0.195, 95% CI: 0038-0978, p = 0.048). Conclusions: The HLA-B * 27 was associated with ankylosing spondylitis, enteropathic but not to spondyloarthritis. The radiological signs of sacroiliitis prevailed in patients positive for HLA-B*27, while intestinal involvement was associated with the absence of this gene. especially in cases of dystrophic scoliosis. In both cases, studies with larger samples are needed to assess whether these trends are evident.